(untitled) (LIS TODAY, 2024)
This study aims at defining the role of academic libraries in supporting the sustainable development goals in the global quest as the United Nations calls for. Academic libraries play important roles in supporting SDGs – particularly Quality Education (Goal 4), Gender Equality (Goal 5), Reducing Inequalities (Goal 10), and Strengthening the Means of Implementation, Partnerships (Goal 17). To this end, this paper seeks to discuss how academic libraries in India can function as a service provider in the achievement of these goals through assimilating their services, collections, and policies into the IDAG. The research explores how these libraries support educational justice, enable the disenfranchised, establish gender parity, and build cooperation through openness and the use of digital tools. However, critical roles notwithstanding, challenges that academic libraries face in India include limited funding sources, digital resource constraints, professional development opportunities, and low levels of networking both nationally and internationally. Additionally, a general lack of understanding of what the libraries can and should do with reference to the promotion of the SDGs limits potential. Besides, the paper also discusses the current research findings regarding the contributions of Indian academic libraries towards sustainable development and adds the strategies for future enhancement for achieving the sustainable development goals by 2030.